Leadership Transformation: Adaptation of a Labor Service Provider Company in the Development of Green Human Resource Management (Study at PT Karya Usaha Baru Sidoarjo-East Java) - Basuni, Basuni; Haryawan, Beny (PT. EQUATOR SINAR AKADEMIA, 2024)
The purpose of this research is to understand the dynamics of leadership transformation in the development of Green HR at PT Karya Usaha Baru, as well as the strategies used to face and manage these changes. The informants in this research are the General Manager, HRD, Operational Staff, Field Coordinators and workers. The research method used a qualitative case study approach, data collection was carried out by in-depth interviews and observations. This research data analysis uses interactive data analysis. The results showed that the leadership plays an important role in the transformation process of GHRM implementation, especially related to strategy formulation. It was also found that the implementation of GHRM Pt Karya Usaha Baru has not been maximized. However, the company has implemented green employee behavior in aspects of recruitment and selection, employee training and development, compensation and benefits, organizational culture, and performance management. Some of the benefits obtained in the implementation of Green HRM are a healthier work environment, building better relationships with partners and getting a positive response by the general public as well as increasing the performance and productivity of the company.